Teaching of Classification - Neelameghan, A.; Bhattacharyya, G. (Journal of Information and Knowledge, 1966)
Points out that today due to the dynamic developments in the universe of subjects, the Classier has to play the role of a Classificationist-in-little from time to time, and that the teaching of Classification should be reoriented to give him this capability. Emphasises that the teaching of classification should be designed to blend the study of the theory and practical work. Gives the steps in preparing the student for the work of classifying and for learning the theory of classification. Suggests that the Postulational Method is helpful in learning practical classification and describes the method. Also emphasises that comparative study of two schemes of classification is helpful to the students in grasping the canons and normative principles of classification. Outlines what should preferably be done in the class and in tutorial. Gives a sample list of subjects about which the student should study, an instruction sheet on how to study, and a sample list of subjects for filiatory grouping.